SHORT REVIEW OF DIRECT ANTERIOR APPROACH VS. LATERAL APPROACH IN TOTAL HIP ARTHROPLASTY - ONE MONTH AFTER SURGERY - Ciriviri, Jasmin Ilija; Vranishovski, Tode; Ciriviri, Dushko; Talevski, Darko (Journal of Morphological Sciences; Vol 8 No 2 (2025): JMS, 2025)
The direct anterior approach (DAA) is gaining use in total hip arthroplasty (THA), while the lateral approach (LA) remains standard. This study compared operative time, blood loss, implant positioning, and early complications in 200 patients (100 DAA, 100 LA). All procedures used cementless implants and tranexamic acid. Mean operative time was longer with DAA (87 vs. 76 minutes), but blood loss and transfusion rates were lower. Radiographs showed similar acetabular positioning; however, varus stem alignment and trochanteric fractures occurred more often with DAA. Early complications included one infection in DAA and three infections plus one dislocation in LA. At one month, Harris Hip Scores favored DAA (94 vs. 81). DAA facilitates faster recovery but requires careful technique and patient selection. Keywords: direct anterior approach, lateral approach, total hip arthroplasty, postoperative X-ray, rehabilitation.